The Influence of Job Satisfaction on Employee Performance and Turnover Intention Through Job Happiness as a Mediating Variable - Danu Pranata, Gita; Setiawan Nugraha, Akbar (Publisher Cv. Inara Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to analyze the effect of job satisfaction on employee performance and turnover intention with job happiness as a mediating variable. The study was conducted on Tunggak Semi “Bamboo Handicraft” employees with a total of 135 respondents, selected using a saturated sampling technique. The data collection method used a Likert scale questionnaire distributed online. Data analysis was carried out using path analysis and the Sobel test. The results showed that job satisfaction had a positive and significant effect on employee performance, job satisfaction had a negative effect on turnover intention, job happiness had a positive effect on employee performance, job happiness had a negative effect on turnover intention, job satisfaction had a positive effect on job happiness, job happiness mediated the effect of job satisfaction on employee performance, and job happiness mediated the effect of job satisfaction on turnover intention. These findings provide important implications for human resource management in efforts to improve employee retention and work performance.